Information System Audit of FIF Mobile Collection at PT Federal International Finance POS Baros Using the COBIT 5 Framework - Aryono, Gagah Dwiki Putra; Aliffito, Sadam Nazar; Permana, Basuki Rahim Setya (JINAV: Journal of Information and Visualization, 2025)
This study aims to evaluate the governance and performance of the FIF Mobile Collection information system implemented at PT Federal International Finance POS Baros using the COBIT 5 framework. As mobile-based applications become critical tools in financial operations—particularly in billing and collection activities—ensuring their security, efficiency, and alignment with organizational goals is imperative. The COBIT 5 framework was adopted to assess the maturity and capability of IT processes, with a specific focus on the DSS05 process: Manage Security Services. Data was collected through observation, interviews, and documentation analysis, and evaluated using the COBIT 5 Process Assessment Model (PAM). The results of the audit show that the DSS05 process achieved Capability Level 3, meaning the process is well-defined and implemented but not yet fully measurable or optimized. The assessment revealed that Levels 1 and 2 were fully achieved, while Level 3 was largely achieved (60–66.66%), indicating the need for performance monitoring and continual improvement mechanisms. Several gaps were identified in the areas of risk management, incident response, and user training, which present potential threats to data security and system reliability. The findings also indicate partial alignment of the system with key enterprise goals such as customer service excellence, operational agility, and information-based decision-making. However, the lack of real-time monitoring, formalized response procedures, and predictive controls hinders the organization from achieving higher governance maturity. Recommendations include implementing automated security tools, conducting regular IT risk assessments, and enhancing user awareness programs. This study concludes that while the FIF Mobile Collection system delivers operational benefits, improvements in governance maturity—guided by COBIT 5—are essential to ensuring secure, efficient, and strategically aligned system performance in the long term.